Tinjauan Yuridis Penjatuhan Pidana Penjara Di Bawah Minimum Khusus dalam Perkara Narkotika (Studi Putusan Nomor 60/Pid.Sus/2022/PN. Tlk jo. Putusan Nomor 564/Pid.Sus/2022/PT. PBR jo. Putusan Nomor 476 K/Pid.Sus/2023) - Refania Rahmitha Adyo; Syarif Nurhidayat (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
Abstract This study examines the imposition of imprisonment below the special minimum sentence in narcotics cases, focusing on the analysis of Decision Number 60/Pid.Sus/2022/PN Tlk jo. Decision Number 564/Pid.Sus/2022/PT.PBR jo. Decision Number 476 K/Pid.Sus/2023. The research highlights the application of Article 114 Paragraph (1) of Law Number 35 of 2009 concerning Narcotics, which stipulates a minimum prison sentence of five years. However, in this case, the Supreme Court imposed a sentence of only three years. This decision raises critical questions regarding the appropriateness of judicial reasoning in imposing a sentence below the statutory minimum and the use of Supreme Court Circular Letter (SEMA) Number 3 of 2015 as a basis for the ruling. The findings of this research conclude that Supreme Court Decision No. 476 K/Pid.Sus/2023 is legally unsound, as it imposed a sentence below the minimum threshold set by law, based on flawed considerations regarding the amount of narcotics evidence the defendant’s status as a repeat offender and the improper application of the aforementioned circular letter.